Em defesa da ruralização do ensino: Sud Mennucci e o debate político e educacional entre 1920 e 1930 - Henrique de Oliveira Fonseca (2014)
Sud Mennucci (1892-1948) was one of the prominent figures of rural education in the first half of the 20th century. His proposals, in defense of a rural education, had wide recognition, especially in the late 1920s and 1930s. This paper seeks to reflect about the trajectory of Mennucci with the objective of to apprehend what were his areas of expertise, his political positions and his ruralist pedagogical project. In order to understand the strategies of the educational debate, I structured this research through of analysis of Mennucci publications in periodicals and newspapers, as well as his own books. Furthermore, this research promotes reflections on the political context of the period and the historiography of education.